Electropolymerization and Electrocatalytic Activity of Poly(4-thienylacetyl-amino-2, 2, 6, 6-tetramethylpiperidinyl-1-yloxy)/(2, 2′-bithiophene) Copolymer. Issue 4 (1st January 2015) - Song, Dandan; Chen, Qiguo; Tang, Danyang; Shen, Zhenlu; Li, Meichao; Ma, Chunan
Abstract : Monomer 4-thienylacetyl-amino-2, 2, 6, 6-tetramethylpiperidinyl-1-yloxy (TATEMPO) has been synthesized. The homopolymer poly(2, 2 ′ -bithiophene) (PBTh), and poly(4-thienylacetyl-amino-2, 2, 6, 6-tetramethylpiperidinyl-1-yloxy)/(2, 2 ′ -bithiophene) (PTATEMPO/BTh) copolymer are successfully prepared on platinum in boron trifluoride diethyl etherate solution by electrochemical polymerization. They are characterized by scanning electron microscopy. The electrochemical copolymerization of TATEMPO and BTh may be accomplished through a radical reaction process. The electrocatalytic oxidation performance of benzyl alcohol in 0.1 M NaClO4 -CH3 CN solution in the presence of 2, 6-lutidine on PTATEMPO/BTh electrode is investigated by cyclic voltammetry and in situ FTIR. Benzyl alcohol is selectively converted to benzaldehyde on the PTATEMPO/BTh electrode, and the overoxidation to benzoic acid is suppressed.